2016
DOI: 10.1371/journal.pone.0152266
|View full text |Cite
|
Sign up to set email alerts
|

COPD Underdiagnosis and Misdiagnosis in a High-Risk Primary Care Population in Four Latin American Countries. A Key to Enhance Disease Diagnosis: The PUMA Study

Abstract: BackgroundAcknowledgement of COPD underdiagnosis and misdiagnosis in primary care can contribute to improved disease diagnosis. PUMA is an international primary care study in Argentina, Colombia, Venezuela and Uruguay.ObjectivesTo assess COPD underdiagnosis and misdiagnosis in primary care and identify factors associated with COPD underdiagnosis in this setting.MethodsCOPD was defined as post-bronchodilator (post-BD) forced expiratory volume in 1 second/forced vital capacity (FEV1/FVC) <0.70 and the lower limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 18 publications
3
55
0
2
Order By: Relevance
“…Lastly, we conducted 3 3 6 several pooled analyses to assess the sensitivity of our findings to alternate definitions of 3 3 7 COPD (fixed ratio and LLN) and analysis methods (unadjusted and adjusted analyses). Except for one study, 23 our findings were consistent.…”
Section: 7supporting
confidence: 80%
See 3 more Smart Citations
“…Lastly, we conducted 3 3 6 several pooled analyses to assess the sensitivity of our findings to alternate definitions of 3 3 7 COPD (fixed ratio and LLN) and analysis methods (unadjusted and adjusted analyses). Except for one study, 23 our findings were consistent.…”
Section: 7supporting
confidence: 80%
“…review, Herrera et al 23 found that respiratory symptoms were not associated with the likelihood of having received a diagnosis of COPD. In the adjusted analysis, these results…”
Section: 7mentioning
confidence: 99%
See 2 more Smart Citations
“…con la baja sensibilidad y especificidad que subyacen a los sín-tomas. Algunos estudios epidemiológicos latinoamericanos demuestran que el diagnóstico clínico de EPOC tiene baja sensibilidad y especificidad 34,35 . Ya que, en consecuencia, no puede asumirse con certeza, que la totalidad de los participantes estuviera diagnosticado de EPOC correctamente, sería muy beneficioso para la comunidad científica si en futuras encuestas nacionales de salud, se pudieran precisar tanto la presencia de enfermedad como la severidad de los síntomas.…”
Section: Discussionunclassified